Habilitando o uso de equipamentos fotográficos por pessoas com deficiências nos membros superiores: um estudo de caso de design participativo de um protótipo de tecnologia assistiva vestível - de Souza, Ricardo Luíz Mendonça; de Freitas, Cintia Rita Soares; Freire, André Pimenta; Delabrida, Saul (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Despite affirmative actions to enable access to higher and secondary education for People with Disabilities (PwD), Brazilian universities still face many limitations to enable the effective inclusion of PwD. Many university spaces lack access to tools to allow PwD to interact with conventional spaces and objects. This article describes the Participatory Design process to develop a prototype interactive assistive technology to enable the use of a photographic DSRL (Digital Single Lens Reflex) camera during practical photography classes in the Journalism degree. The student, who actively participated as a researcher, has a motor disability with low fine motor skills and little muscular resistance in the upper limbs. Results include the design implications derived from developing inclusive interfaces generated through sketches . The study employed the Directed Fantasy method to compose the Interface Design. As a product of the design process, we present the implementation of this prototype interface as an assistive technology to enable the interaction as a piece of wearable technology. The paper presents contributions with the discussion of novel implications for the design of wearable assistive technologies using participatory design, with aspects that involve both hardware and software. It also contributes to improving the access of people with motor disabilities to arts and photography, as areas with scarce assistive technology.